Capaian Penerimaan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Tahun 2018-2022 Di Desa Sukamanah Kabupaten Bekasi - Yani, Yani; Dahuri, Adin (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Tax payers of Sukamanah Sub District in Bekasi Regency usually pay their Land and Building of Rural and Urban Tax (PBB-P2) in three ways, namely paying themseves directly to the bjb Bank of Cikarang, entrusting the payment collectively to tax collector Officer and online payment using the